ADAKAH NIAT MAHASISWA UNTUK BERWIRAUSAHA? (Studi Empirik pada Mahasiswa Universitas YARSI)
Drawing the theory of planned behavior, the main objective of this study was to identify the students’ entrepreneurial intentions using double linear regression test. The sample of this study consisted of total 281 undergraduate students, divided into two categories, the economics faculty and non – economics faculty. The result shows that among three variables – subjective norms, attitude towards entrepreneurship, and perceived behavioral control- subjective norms is the strongest predictor of intentions within the economics students, while among the non – economics students, attitude is the strongest. However, the research revealed that all of the variables have a positive and significance influence on entrepreneurial intentions both for the economics and non-economics students. Despite its limitation, this study wishes to make contribution and implication to the literature of entrepreneurship. This study might help students and universities to take action in improving entrepreneurial intentions